Changes in Pisum sativum L. Plants and in Soil as a Result of Application of Selected Foliar Fertilizers and Biostimulators - Hanna Sulewska; Alicja Niewiadomska; Karolina Ratajczak; Anna Budka; Katarzyna Panasiewicz; Agnieszka Faligowska; Agnieszka Wolna-Maruwka; Leszek Dryjański (Agronomy, 2020)
The aim of this study was to assess the effect of selected biostimulators and foliar fertilizers on plant development, plant yield, soil fertility and soil biochemical activity (dehydrogenases, phosphatases, catalases) during the cultivation of pea (Pisum sativum L.). A field experiment was conducted between 2016 and 2018 at the Gorzyń Experimental and Educational Station, Poznań University of Life Sciences in Poland. The following treatments were tested: (1) control; (2) Titanit; (3) Optysil; (4) Metalosate potassium; (5) Rooter; (6) Bolero Mo; (7) Adob Zn IDHA; (8) Adob B and (9) Adob 2.0 Mo. Adob Zn IDHA stimulated yields, especially under average moisture conditions and less so in drought conditions, and the differences compared to control amounted 8.36 and 4.3%, respectively. The results showed a close relationship between the effects of the biostimulators and foliar fertilizers and weather conditions during the study. It was not possible to determine whether any of the biostimulators or foliar fertilizers had a positive effect on pea seed yield in any year. Similarly, it was difficult to clearly determine the effect of the biostimulators and fertilizers on biochemical activity in the soil, although soil enzyme activity was influenced most by application of the Bolero Mo fertilizer. In all study years, biological nitrogen fixation was always greater after the application of a biostimulator/fertilizer treatment.